2006
DOI: 10.1038/sj.bjc.6603047
|View full text |Cite
|
Sign up to set email alerts
|

XELOX (capecitabine plus oxaliplatin) as first-line treatment for elderly patients over 70 years of age with advanced colorectal cancer

Abstract: The purpose of this phase II trial was to determine the efficacy and safety of the XELOX (capecitabine/oxaliplatin) regimen as firstline therapy in the elderly patients with metastatic colorectal cancer (MCRC). A total of 50 patients with MCRC aged X70 years received oxaliplatin 130 mg m À2 on day 1 followed by oral capecitabine 1000 mg m À2 twice daily on days 1 -14 every 3 weeks. Patients with creatinine clearance 30 -50 ml min À1 received a reduced dose of capecitabine (750 mg m À2 twice daily). By intentto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(55 citation statements)
references
References 50 publications
4
49
0
2
Order By: Relevance
“…The feasibility and activity of the XELOX regimen in elderly patients has also been investigated: a 37% response rate, with 8.5 months of median progression-free survival and 14.4 months of median survival, have been reported (Comella et al 2005). These Wndings were subsequently conWrmed by Feliu et al (2006), who reported a 36% response rate, a median progression-free survival of 5.8 months, and an overall survival of 13.2 months.…”
Section: Introductionmentioning
confidence: 81%
“…The feasibility and activity of the XELOX regimen in elderly patients has also been investigated: a 37% response rate, with 8.5 months of median progression-free survival and 14.4 months of median survival, have been reported (Comella et al 2005). These Wndings were subsequently conWrmed by Feliu et al (2006), who reported a 36% response rate, a median progression-free survival of 5.8 months, and an overall survival of 13.2 months.…”
Section: Introductionmentioning
confidence: 81%
“…Subsequently, irinotecan was not widely used as a second-line therapy (18). Therefore, it may be necessary to increase the proportion of elderly to whom second-line treatment is administered following disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…The median OS was 13.2 months (95% CI 7.6-16.9 months). There were 14 (28%) patients who exhibited Grade ≥3 adverse reactions including 11 (22%) with diarrhea, 8 (16%) with asthenia, 7 (14%) with nausea/vomiting, 3 (6%) with neutropenia, 3 (6%) with thrombocytopenia and 2 (4%) with hand-foot syndrome (20). Based on the data from these trials, capecitabine and oxaliplatin may be regarded as an appropriate treatment selection for elderly patients with MCRC.…”
Section: Study (Year Reference) Pfs (Month) Median Os (Month) ------mentioning
confidence: 99%